Open Problem-Based Learning (OPBL) Scenario on 2D Text Animation Using Polya Approach - Untari, Rahmania Sri; Liansari, Vevy; Su’udiah, Firdaus (Universitas Negeri Malang, 2020)
Animation, with its various roles, has become a crucial technology of science. The roles of OPBL is to provide students with opportunities to exercise creative thinking, express critical ideas, build collaboration skill and use technology which will add their value at workplace as well as in real life. The research is conducted to compare students’ problem-solving skill before they received OPBL treatment and after they did. The research was conducted using the quasi-experiment method. Paired sample t-test examination was used to analyze the data. The research suggested that there is a significant difference in the students' problem-solving skill before they received OPBL treatment and after they did, and that the difference is highly influenced by the syntax or learning model scenario. Cooperative learning made student group learning more structured in alignment with the learning topic assigned.